Identification of artefact contamination morphological characteristics in minimizing pitfalls in cytology / Nur Hanina Mohd Rahaman - Mohd Rahaman, Nur Hanina (2015)
INTRODUCTION: Pitfall in cytomorphological diagnostic can be defined as misdiagnosis or misinterpretation of result which may lead to false positive or negative thus affected treatment and caused possible morbidity· The occurrence error during the cytomorphological diagnosis is an artifact contaminant. The possible artifact contaminants interference in the cytological slides might derived from patients, medical laboratory technologist and laboratory environment. The sources of artifact contaminant are lipsticks, pubic hairs, cotton fibers, KY Gel lubricant, compact powder, dust particles, gloves powder, pencil carbon and mascara. The general objective of this study is to determine the morphological characteristics of artefacts contaminant in cytological sample that can cause pitfalls in diagnostic. METHODS: The selected artefact contaminants were collected and put in the sterile container, containing normal human sputum as an adherence medium. Prepared slides were then stained using Papanicolaou (Pap) and May-Grunwald Giemsa (MGG), screened and the result were recorded by capturing the image using Leica DM750 Microscope equipped with an ICC 50 HD camera. Finally, the findings were compared to the normal, malignant and microorganisms cells via an establish cytology atlas and confirmed by qualified cytoscientists. RESULTS: The lipstick contaminant resemble tumor diathesis in present of malignancy background. Meanwhile, the pubic hairs resemble Wuchereria bancrofti parasite. The cotton cloth were resemble the Leptothrix bacteria. The KY Gel lubricant resemble to the mucus appearance. The compact powder has similar appearances to the comflaking artefacts. The dust particles resemble the keratotic cell. The gloves powder resemble with the cells in atrophic menopausal smear. The pencil carbon and mascara characteristics similar with the anthracotic pigment in black lung disease smears. CONCLUSION: The some morphological characteristics of artifact contaminants can mimic cytomorphological of human cells and these findings can be used as a reference in cytomorphological diagnostic to minimize a pitfall.